2018
DOI: 10.1590/01047760201824032584
|View full text |Cite
|
Sign up to set email alerts
|

THREE EPICORMIC SHOOT TECHNIQUES IN I. paraguariensis MOTHER TREES AND ITS CUTTING ACCORDING TO THE MATERIAL REJUVENATION DEGREE

Abstract: techniques in I. paraguariensis mother trees and its cutting according to the material rejuvenation degree. CERNE, v. 24, n. 3, p. 240-248, 2018. HIGHLIGHTS Semi-girdling technique produces longer epicormic shoots in native Ilex paraguariensis. Cuttings form epicormic shoots produce a higher number of roots than treetop shoots. Shoots from detached live branches have short length with high number of leaf buds. New studies are needed regarding techniques to elongate shoots from detached branches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 13 publications
1
24
0
2
Order By: Relevance
“…The application of the complete girdling technique on I. paragauriensis trees to promote epicormic sprouts emission rarely leads to their death (Santin et al, 2008b). The species has a great capacity for healing this type of injury (Nascimento et al, 2018), what was also observed in this experiment.…”
Section: Experiments Of Mother Trees Fertilizationsupporting
confidence: 80%
See 4 more Smart Citations
“…The application of the complete girdling technique on I. paragauriensis trees to promote epicormic sprouts emission rarely leads to their death (Santin et al, 2008b). The species has a great capacity for healing this type of injury (Nascimento et al, 2018), what was also observed in this experiment.…”
Section: Experiments Of Mother Trees Fertilizationsupporting
confidence: 80%
“…Considering the sprouts vegetative growth from cited works (Lourenço et al, 1997;Santin et al, 2008b;Santin et al, 2013) and comparing to those obtained by Nascimento et al, 2018 and this work (same study area), a significant difference can be noticed. The cited authors bring a higher percentage of sprouts emission, of greater number and length, even for the least representative treatments, when compared to this work.…”
Section: Experiments Of Mother Trees Fertilizationmentioning
confidence: 62%
See 3 more Smart Citations